Lack of Effect of Rivipansel on QTc Interval in Healthy Adult African American Male Subjects. (16th May 2017) - Tammara, Brinda K.; Plotka, Anna; Shafer, Frank E.; Readett, David R. J.; Riley, Steve; Korth‐Bradley, Joan M.
Abstract: Rivipansel is a pan‐selectin inhibitor in phase 3 development for the treatment of vaso‐occlusive crises in patients with sickle cell disease. This single‐dose, randomized, 3‐period, 3‐treatment (400 mg moxifloxacin open‐label, 4 g rivipansel–blinded, and placebo‐blinded) crossover study evaluated the effect of rivipansel on the QT/QTc interval in 48 healthy male African American subjects (age, 21–53 years; weight, 60–115 kg). Time‐matched, placebo‐adjusted change from baseline QT interval using Fridericia's correction method (QTcF) was determined using a repeated‐measures mixed‐effects model. The highest upper bound of the 2‐sided 90% confidence interval (CI) for QTcF change was 3.22 milliseconds 3 hours postdose. Moxifloxacin showed the anticipated QTcF effect, indicating that the study had adequate sensitivity to detect changes in the QTcF interval. The study concluded that no QTcF effect was demonstrated with rivipansel compared with placebo, as the upper bound of the 2‐sided 90%CI was less than 10 milliseconds at all times. Exposure–response modeling for rivipansel concentrations and change from baseline in QTcF data corroborated a lack of effect with rivipansel compared with placebo. Single doses of rivipansel 4 g by intravenous infusion over 20 minutes were well tolerated in this study.